The effects of smartphone use as a risk factor for dry eye disease in children - خلوف بتول; درويش تيم (Latakia University Journal -Medical Sciences Series, 2023)
Purpose: Studying the effect of smartphone use on the development of dry eye disease in children. Methods: The research included 200 children who use smartphones, from the ophthalmology department at Tishreen University Hospital in Lattakia during the period between 2022-2023 who met the study criteria. They were classified into two groups (dry eye, without dry eye), according to the diagnostic criteria for dry eye.The ages of the participants ranged from 5 -17 years. A comprehensive ophthalmological examination was performed: visual acuity, best corrected visual acuity, refractive errors, slit-lamp examination of the anterior sections (eyelids - conjunctiva - cornea), tear film break-up time (BUT), Schirmer test, blink rate while using the smartphone, questioning about the symptoms of the ocular surface disease index OSDI, a questionnaire designed to collect information about the number of hours the VDT is used, Then the results between the two groups were compared. Results: The prevalence of patients with dry eyes was 7.5%, compared to 92.5% of children without dry eye. There was a statistically significant increase in the average hours of smartphone use in the dry eye group (P = 0.008). Evaluation of tear function revealed significant differences between the two groups. The OSDI increased, while the BUT and Schirmer values decreased in the dry eye group (P = 0.001, P = 0.001, P = 0.001, respectively). The study also showed a decrease in blink rate during smartphone use in the research sample, without a statistically significant difference between dry eye and no dry eye groups (P = 0.1). Conclusion: The prevalence of dry eye among healthy children who use smartphones in the research sample was 7.5% . We also found a statistically significant increase in the average number of hours of smartphone use in children with dry eye.As well as statistically significant changes in dry eye tests (BUT, ST, OSDI).A decrease in blink rate during smartphone use. Key words: dry eye in children, smartphones, blink rate, dry eye